Law and Technology: Legal Technology Model under the Authority of the Indonesian Notary Position in the Industrial Revolution Era 4.0 - Unggul Basoeky; Fx Joko Priyono; Siti Malikhatun Badriyah; S Sukirno (LEGAL BRIEF, 2021)
The era of the Industrial Revolution 4.0 has changed the old paradigm and standard values quickly. Likewise, the legal aspect cannot be separated from the demand to transform every concept, value and paradigm. On the public law side, each country is required to reform its legal rules to be adaptive and compatible with the development of the 4.0 era, while on the private law side it has an impact on trade transaction practices that have created new platforms, namely e-commerce and e-contracts. The position of a notary as a part of the legal system cannot avoid the disruption of the development of the industrial revolution. The preservation of the old paradigm of the position of a notary that requires it to be done traditionally should be reconstructed immediately so that the practice of office can develop and meet the demands of the times. This study uses a normative juridical research method through a conceptual approach, a statutory approach and a legal history approach which is elaborated with the concept of disruption technology and the theory of the economic analysis of law. Conclusion This journal describes that the fundamental obstacle to notary practice based on the Legality Principle which relies on Procedure, Authority & Substance should have been able to be transformed electronically based on the legal technology paradigm. With references from various organizational benchmarks and conventions mentioned above, they can be the philosophical, sociological and normative foundations in formulating notarial laws that are compatible, adaptive and adequate to the realities of the industrial revolution era 4.0. Recommendations for the need for legal reform, namely changes to legislation concerning the position of a notary through the establishment of an e-notary PP that integrates in a rigid manner the procedure, substance and authority in applying the authority of a notary in certifying electronic transactions.